User experience on educational websites’ search engine. - Mahmud, Murni; Hussein, Idyawati; Abd Malik, Sofianiza (IIUM Press, 2011)
This paper reports a user experience study on using search engine. Which was conducted on selected universities' websites. The study aims to evaluate the user experience of the search engine. Results indicate that many educational uebsites in Malaysia may require better search engine for improving the user experience kvhen searching for information. The adverse rating is due to scarch engine poor usability. Ne\-ertheless. users continued browsing and navigating the websites to complete the task at hand - to search for related courses on Human Computer interaction with related keylvords. Regardless the low engagement lec.el. users rating on overall usability on websites is still high due to satisfying experience with other parts of the websites